Young plasma transfer recovers decreased sperm counts and restores epigenetics in aged testis - Erdogan, K.; Ceylani, Taha; Teker, H.T.; Şengil, A.Z.; Uysal, F. (Elsevier Inc., 2023)
Background and aim: Aging is one of the causes of male infertility, and abnormal global DNA methylation and imprinting defects have been characterized in testis during biological aging. One of the important emerging approaches aims to take advantage of the healing properties of young blood plasma to limit the progression of aging in various organs in the body. We aimed to show whether blood plasma transfer has an effect on DNA methylation and spermatogenetic cell development. In addition, we aimed to show whether the young plasma transfer to old mice has an effect on the rejuvenation of the old and whether the impaired DNA methylation and PCNA expression in old age can be restored. Methods: Groups were (i) young control, (ii) young plasma transfer to aged, (iii) aged control, (iv) aged plasma transfer to young. We utilized IHC and WB in protein level of Dnmts. For the global DNA methylation level, we used 5-methylcytosine staining. We also analyzed PCNA protein expressions in all groups by IHC. Results: We found that transfusion of young plasma into the old animal restored DNA methylation and PCNA expression as it did in the young animal. Most importantly, we observed an increase in spermatogonia and spermatid counts in older animals after young blood plasma transfer. Conclusions: Our findings show that young plasma transfer can restore epigenetic disorders that occur with aging and solve infertility problems by increasing the sperm count that decreases. It needs to be supported by different studies, especially human studies. © 2022 The Authors
Keywords: Blood plasma transfer; DNA methylation; Dnmt; Spermatogenetic cell stages; Testes; DNA (cytosine 5) methyltransferase 1; DNA methyltransferase; DNA methyltransferase 3A; DNA methyltransferase 3B; DNA methyltransferase 3l; unclassified drug; aged; aging; animal tissue; Article; controlled study; DNA methylation; epigenetics; immunohistochemistry; male; nonhuman; plasma exchange; protein expression; rat; sperm count; spermatogonium; Sprague Dawley rat; testis; Western blotting